Lingkar pinggang dan lingkar leher dengan kadar kolesterol total pada wanita usia subur obesitas - Rifial Ramadhan Manik; Nurmasari Widyastuti; Choirun Nissa (Jurnal Gizi Klinik Indonesia, 2019)
Waist circumference, and neck circumference correlated to total cholesterol among reproductive-age women with obesity